Outside the cuckoo's nest: investigating the reasons behind African male engineering students' under-utilization of mental health services - Samouilhan, Tanya (My University, 2010)
ABSTRACT It has been found that the under-utilization of mental health services in South Africa is particularly concentrated among young, African males. This population group is also significantly at risk for suicide due to their exposure to stressors said to be related to the development of psychological disorder. Therefore, exploration into their reason(s) for this under-utilization, as well as the identification of their preferred alternate treatments and/or coping mechanisms, is crucial for future efforts to improve mental health care in South Africa. This study thus endeavoured to investigate these issues among a group of young, African males. The sample comprised eight African males between the ages of 18 to 21 years of age. The participants were first year Engineering students at the University of the Witwatersrand. Individual interviews were conducted with each participant according to a semi-structured interview schedule which was developed and piloted by the researcher. A thematic content analysis was employed to uncover these reasons, alternate treatments and coping mechanisms. The results illustrate that the alleged barriers to seeking professional psychological treatment in South Africa for young, African males include strong beliefs in an African cultural ideology; beliefs supporting hegemonic male gender roles; the accumulative beliefs of an African male gender role; mental illness stigma; negative indirect contact via stigmatising media representations of mental illness; and the difficulty discerning between normal distress and abnormal psychological disorders. There also emerged discrepancies between the help-seeking pathways the participants would recommend for themselves and those that they would suggest for other people. Furthermore, the participants provided examples of alternate treatments which are used more often and are more preferable as modes of treatment for African males. However, the limited number of alternate treatments and the excessive reliance on negative coping mechanisms highlight the importance of the greater need for appropriate, relevant mental health services for young, African males in this country.